Structure and property changes of soybean protein isolates resulted from the glycation and cross-linking by transglutaminase and a degraded chitosan. Issue 1 (2nd January 2016) - Zhu, Chang-Yue; Liu, Hong-Fang; Fu, Miao; Zhao, Xin-Huai
Abstract : A glycated and cross-linked soybean protein isolate (GC-SPI) with the glucosamine content of 19.40 g/kg protein was prepared by using SPI, transglutaminase, and a degraded chitosan under fixed conditions, aiming to assess modified properties and potential application of GC-SPI. GC-SPI has less reactable –NH2 groups than SPI (0.38 versus 0.48 mol/kg protein), and is verified by electrophoretic analysis to be a glycated and cross-linked protein product. Infrared spectroscopy and circular dichroism analyses demonstrate that GC-SPI contains more –OH groups, and has a more open secondary structure. In comparison with SPI, GC-SPI has higher surface hydrophobicity but lower in vitro digestibility due to protein cross-linking, and exhibits greater water- and oil-binding capacities (9.9 versus 6.4 and 3.7 versus 2.0 kg/kg protein). It is concluded that the glycation and cross-linking confer an open structure and modified properties of SPI, and GC-SPI is a potential ingredient with better hydration and oil-binding than SPI.